Informativni izračun kot pravni presadek: od dohodnine do socialnih pravic - Babšek, Matej (Podjetje in delo, 2021)
Since 2007, the informative calculation of personal income tax has introduced simplifications for all participants in the procedure in numerous foreign countries as well as Slovenia. More importantly, the collection of this tax in terms of correct assessment has improved. Within the theory of legal transplants, i.e. transfer of institutes from one field to another, this paper examines the idea of importing the calculation from the tax to the social field. The central method of research is the analysis of case law on the informative calculation of personal income tax, which showed that there are no systemic considerations against such a transplant. On the other hand, there are various advantages, e.g. the quantity of social procedures, their continuity, protection of procedural rights, and at the same time sectoral public benefits, as well as pursuing the strategic foundations of this institute in the latest social reform in 2018. The findings presented herein are applicable to both the legal theory and policy makers and practitioners in the fields of taxes and social protection.
Keywords: case law; davčni postopek; informational personal income tax calculation; informativni izračun dohodnine; legal transplant; pravni presadek; social rights; socialne pravice; sodna praksa; tax procedure